2023
DOI: 10.1093/brain/awad037
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing reactive astrocyte-neuron interaction in Alzheimer’s disease using 11C-acetate and 18F-FDG

Abstract: Reactive astrogliosis is a hallmark of Alzheimer’s disease (AD). However, a clinically validated neuroimaging probe to visualize the reactive astrogliosis is yet to be discovered. Here, we show that PET imaging with 11C-acetate and 18F-fluorodeoxyglucose (18F-FDG) functionally visualizes the reactive astrocyte-mediated neuronal hypometabolism in the brains with neuroinflammation and AD. To investigate the alterations of acetate and glucose metabolism in the diseased brains and their impact on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
4
12
1
Order By: Relevance
“…3c, d). Furthermore, consistent with our previous findings in the brain 27 , we found that the increase in tonic GABA current was significantly reduced to a normal level by preincubation of acute spinal cord slices with MAOBi (100 nM; Fig. 3c, d).…”
Section: Snl Induces Astrocyte Reactivity In the Ipsilateral Spinal D...supporting
confidence: 93%
See 1 more Smart Citation
“…3c, d). Furthermore, consistent with our previous findings in the brain 27 , we found that the increase in tonic GABA current was significantly reduced to a normal level by preincubation of acute spinal cord slices with MAOBi (100 nM; Fig. 3c, d).…”
Section: Snl Induces Astrocyte Reactivity In the Ipsilateral Spinal D...supporting
confidence: 93%
“…Reactive astrocytes excessively release GABA in the dorsal horn Accumulating lines of evidence indicate that reactive astrocytes can excessively synthesize and release the inhibitory transmitter GABA in various brain regions 16,25,26 , which, in turn, can decrease neuronal activity and glucose metabolism 15,27 . Thus, we investigated whether reactive astrocytes in the spinal cord also synthesize excessive GABA in a neuropathic pain model.…”
Section: Snl Induces Astrocyte Reactivity In the Ipsilateral Spinal D...mentioning
confidence: 99%
“…9,10 In contrast to tumor-directed amino acid radiotracers, 11 C-acetate (ACE) targets reactive astrogliosis in the tumor microenvironment (TME) and has been associated with reactive astrocytes under inflammatory conditions in the CNS. [13][14][15] Previous studies have confirmed that 11 C-ACE uptake is attributable to reactive astrocytes via monocarboxylate transporter 1 at the tumor boundary. 16 As an imaging tracer for reactive astrogliosis, high C-ACE uptake has been significantly associated with high-grade gliomas and poor prognosis.…”
mentioning
confidence: 93%
“…A recent PET study, which combined acetate- and FDG-PET, demonstrated that reactive astrogliosis is associated with decreased glucose utilization in AD. 25 With regard to brain energy metabolism related to astrocytes, lactate has emerged as a key molecule, given the reliance of astrocytes on glycolysis and their propensity to produce lactate. 24 We recently demonstrated increased lactate levels in the PCC and their association with increased myo-inositol levels by using an advanced MRS sequence in patients with AD.…”
Section: Introductionmentioning
confidence: 99%